The Effect of Hedonic Shopping Value, Utilitarian Value, and Store Atmosphere on Impulse Buying in Minnisou Lippo Plaza Kendari - Waode Maratun Shaleha; Nisrina Hamid; Al Asy Ari Adnan Hakim (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2020)
The purpose of this research is to analyze the effect of hedonic value, utilitarian value and store atmosphere on impulse buying. The population in this study were consumers in Kendari City who had shopped and visited Minnisou Lippo Plaza Kendari. The population in this study is infinite which means unlimited. The number of samples in this study amounted to 96 respondents (based on the Lemeshow formula). Data analysis method in this research uses multiple linear regression. The results showed that hedonic shopping value has a positive effect on impulse buying, utilitarian value does not have a positive effect on impulse buying, store atmosphere has a positive effect on impulse buying, and hedonic shopping value, utilitarian value and store atmosphere together positively influence positive impulse buying.